Storage as a service offering guide - Lonzer, Hartmut; Standau, Markus; Gucer, Vasfi (IBM Redbooks, 2021)
IBM® Storage as a Service (STaaS) extends your hybrid cloud experience with a new flexible consumption model enabled for both your on-premises and hybrid cloud infrastructure needs, giving you the agility, cash flow efficiency, and services of cloud storage with the flexibility to dynamically scale up or down and only pay for what you use beyond the minimal capacity. This IBM Redpaper provides a detailed introduction to the IBM STaaS service. The paper is targeted for data center managers and storage administrators.
Online resource; title from title details screen (O'Reilly, viewed February 15, 2022)
Keywords: Storage area networks (Computer networks); Virtual storage (Computer science); IBM computers; Réseaux de stockage (Informatique); Ordinateurs; Mémoires virtuelles; IBM (Ordinateurs)